AN INVESTIGATION OF THE CONTRIBUTIONS OF CITY COUNCILS TO THE URBAN MANAGEMENT: ELAZIĞ SAMPLE - Murat AYGEN (Fırat University, 2019)
The role of city councils in our country is getting more day by day. This councils is strongest participating mechanizm of enstrument that determine and solve primary problems of cities . City councils must be argued in evolution, working, maintainability, activity and different dimensions as part of multijoint and moltiactors. In this case, scientists working “City Councils”, “Participating to” “Decision Making Mechanizms’’ and “Local Agenda Process of 21”, city council volunteers and operators, related governmental department sagents, civil society agents must share their knowledge and experiences. City councils contribute city life. Hence we have to struggle for development of city councils. Because cities are our. We live in cities now. İn the future our children, descendants and generations will live too. In this issue, only in